Weaving rapport: doctors’ strategies towards patients’ noncompliance - Yinong Tian; Jing Zhang; Haiyang Che; Yonggang Su (BMC Health Services Research, 2023)
Abstract Background A successful therapeutic rapport between doctors and patients is built on effective doctor-patient communication. Noncompliance of patients which challenges their communication has been described in the research, yet the rapport strategies are not well discussed. Methods This qualitative study investigates the rapport strategies when doctors face noncompliance in consultations and its pragmatic effects achieved through the doctors’ speeches. The 10-hour recordings come from the doctor-patient communication in the hospital setting. Thereafter, we analyze their conversation following the Spencer Oatey’s rapport management model. Results Compliments and joking in the illocutionary domain, storytelling in the discourse domain, the doctors’ participation in the participation domain and the choice of appropriate titles in the stylistic domain are identified and analyzed as the rapport-building strategies. Conclusion The present study has offered insights into physicians’ rapport-building strategies in the face of rapport-threatening behavior from patients. These strategies will help the doctors to deal with rapport-challenging behavior and boost overall patient wellness.